Detection of measles virus RNA in urine specimens from vaccine recipients - Paul A. Rota; Ali S. Khan; Edison Luíz Durigon; Thomas E. Yuran; Y Villamarzo; William J. Bellini (1995)
Analysis of urine specimens by using reverse transcriptase-PCR was evaluated as a rapid assay to identify individuals infected with measles virus. For the study, daily urine samples were obtained from either 15-month-old children or young adults following measles immunization. Overall, measles virus RNA was detected in 10 of 12 children during the 2-week sampling period. In some cases, measles virus RNA was detected as early as 1 day or as late as 14 days after vaccination. Measles virus RNA was also detected in the urine samples from all four of the young adults between 1 and 13 days after vaccination. This assay will enable continued studies of the shedding and transmission of measles virus and, it is hoped, will provide a rapid means to identify measles infection, especially in mild or asymptomatic cases.